KEDUDUKAN LESSOR DALAM PERJANJIAN OPERASIONAL LEASING TERHADAP KEPAILITAN LESSEE DI INDONESIA - Mahmudah, Siti (Diponegoro Private Law Review, 2018)
Operational leasing is one of the financing sources that can be used by entrepreneurs to meet the need for capital goods. The parties are Lessors and lessees. Debt settlement of the lessee as a debtor may be settled through a bankruptcy institution resulting in a general seizure of the debtor's property. This study aims to determine the position of Lessor for leased capital goods, and unpaid rent in the insolvency of the lessee with the normative juridical approach method which is based on the secondary data analyzed qualitatively. Baramg capital in bankruptcy lesse not boedel bankrupt, lessor is its owner and domiciled as creditor holder of privilege of unpaid rent as regulated in Article 1139 Civil Code. Keywords : Lessor, Lesse, Bankruptcy